Robótica Educativa como estrategia para el desarrollo del pensamiento computacional en los estudiantes de décimo año de Educación General Básica en la Unidad Educativa Particular “Santa Mariana de Jesús”, de la ciudad de Loja, periodo 2021-2022. - Quezada Vera, Lida Andreina (2022)
The role of education is to prepare human beings for challenges, needs and opportunities in a globalized world, therefore, the aim of this research work is to develop computational thinking so that students acquire an active and creative role in the use of innovative and interactive technologies where learning methods are ludic, based on the principles of interaction, collaborative work, creativity and educational approach. Considering this framework, this research uses a quantitative methodology, the data were collected through a survey and a questionnaire, which was applied in two different stages: at the beginning (PreTest) and at the end (PostTest) of the process. Regarding the tabulation of data, a rubric was used to evaluate the abilities of Computational Thinking which showed results before and after the investigation. These data allowed not only a comparison and analysis of the implementation of the project to be made but also revealed an increase in skills. Moreover, to promote skills’ development, the STEAM Instructional Framework methodology was used, this framework comprises the following phases: understand, imagine, design, build, approve and improve. Therefore, the results obtained show an increase in computational thinking skills since the indicators changed from Fair to Very Good. Consequently, it can be concluded that computational thinking fostered through educational robotics results in enriching learning that guarantees holistic and comprehensive cognitive development. Key words: Education, Computational thinking, Educational robotics, Innovation, Creativity.